Study on air pollutant emission inventory of port operation machinery in container terminal - Li Mingjun; Yang Xiaowen; Li Yue; Zhang Liguo; Bao Zhiyuan; Zhang Yonglin; Cheng Jinxiang; Xu Honglei (E3S Web of Conferences, 2021)
In this paper, a calculation method system of air pollutant emission inventory of port operation machinery in container terminal is established. Through the special investigation of port machinery manufacturers and engine manufacturers, the average load rate data of main port machinery engines in domestic container terminals are obtained. Taking a domestic container terminal as an example, the dynamic method and fuel consumption method are used to calculate the air pollutant emission inventory of port operation machinery, and the calculation results of the two methods are compared and analyzed. The results show that the calculation method system of air pollutant emission inventory of port operation machinery established in this paper is highly practical, and the calculation results obtained by the two methods are very close.